Total organic halogen (TOX) analysis in waters: A short review. Issue 1 (31st December 2023) - Wu, Jing; Wang, Yunwen; Gong, Xuexin; He, Mei; Wang, Xiaoli; Zhao, Rusong; Hao, Zhineng; Liu, Jingfu
ABSTRACT: Halogenated organic compounds (HOCs) are prevalent in environmental waters, but current analytical techniques are unable to identify and quantify all individual HOCs. To enhance the understanding of unregulated and unknown HOCs, total organic halogen (TOX) is proposed as a total quantity index for the overall content of HOCs in waters, and has achieved significant progresses. This paper presents a review of TOX analysis from perspectives of detection and pretreatment methods, including the measurement of halide ion (IX) or TOX content by several instruments; separation methods with enrichment based on activated carbon-adsorption, solid-phase extraction, and liquid-liquid extraction, as well as without enrichment based on the subtraction method and IX removal. The relevant fundamentals, operational processes, and key influencing factors are especially concerned. This review should be useful in understanding TOX analysis and the risk of HOCs in waters, and calls for developing more efficient TOX measurement approaches in the future. GRAPHICAL ABSTRACT: uf0001